Chemoradiotherapy or Induction Chemotherapy Followed by Chemoradiotherapy. University Hospital Fuenlabrada: Our Experience in 10 years. (Global Journal of Medical Research, 2017)
Abstract not found
Keywords: chemoradiotherapy; induction chemotherapy; head and neck; survival; locally advanced